Fused Deposition Modeling of Poly (lactic acid)/Macadamia Composites—Thermal, Mechanical Properties and Scaffolds - Song, Xiaohui (Materials (Basel), 2020)
In this work Macadamia nutshell (MS) was used as filler in fused deposition modeling (FDM) of Poly (lactic acid) (PLA) composites filaments. Composites containing MS both treated and untreated with alkali and silane were investigated by means of Fourier transform infrared spectroscopy (FTIR), X-Ray diffraction (XRD), Thermogravimetry (TG), scanning electron microscopy (SEM). The results showed that the treated MS composites had better thermal stability. Furthermore, compression tests were carried out. The PLA with 10 wt% treated MS composite was found possessing the best mechanical properties which was almost equivalent to that of the pure PLA. Finally, porous scaffolds of PLA/10 wt% treated MS were fabricated. The scaffolds exhibited various porosities in range of 30–65%, interconnected holes in size of 0.3–0.5 mm, micro pores with dimension of 0.1–1 μm and 37.92–244.46 MPa of elastic modulus. Those values indicated that the FDM of PLA/MS composites have the potential to be used as weight lighter and structural parts.